A Behavioral Classification Framework for Orthodontic Patients: Understanding Demand, Compliance, Trust, and Treatment Response - Savio, Shifo; Sreenivasagan, Swapna; Balasubramaniam, Arthi (Journal of Neonatal Surgery, 2025)
Background: The emphasis on both practical and esthetic results has led to a substantial evolution in orthodontic therapy. However, patient behaviour has a big impact on treatment success. This includes compliance, treatment desire, and trust in orthodontists. Based on these behavioural characteristics, orthodontic patients can be categorised in an organised way to improve outcomes and provide more individualised care.This study aims to develop a behavioral classification framework for orthodontic patients based on their treatment demand, trust in the orthodontist, compliance with treatment protocols, and treatment response. Materials and Methods: A cross-sectional study was conducted among 100 orthodontic patients evaluated by their treating orthodontists and residents. A structured questionnaire assessed patient demand, trust, and compliance. Content validity ratio (CVR), content validity index (CVI), inter-rater, and intra-rater reliability analyses were performed. Data were statistically analyzed using SPSS. Results: Patients were classified into five categories: Idealists – High-demand, trusting, compliant, and positive responders. Inconsistents – Moderate-demand, trusting, partially compliant, and variable responders. Skeptics – Low-demand, distrustful, non-compliant, and limited responders. Strugglers – High-demand, trusting, non-compliant, and moderate responders. Unpredictables – Moderate-demand, trusting, compliant, but with unpredictable responses. Statistical analyses confirmed the validity and reliability of the classification system. Conclusion: The proposed behavioral classification provides a structured approach to understanding orthodontic patient behavior. It enables clinicians to tailor treatment strategies, improve patient adherence, and enhance overall treatment outcomes. Future research should explore interventions to optimize compliance in different patient categories.